Phytochemical and Biological Evaluation and Isolation of Quercetin from Hypericum cordifolium Flower - Khatri, Janak; Gautam, Gita; Dhoubhadel, Kusum Maiya; Rajbhandari , Meena (Scientific World, 2023)
Hypericum cordifolium is a medicinal plant used in the treatment of various ailments in Nepalese traditional medicine. The medicinal values and bioactive constituents of Hypericum perforatum have been well investigated and is used as an alternative medicine in the treatment of depression, cancer, inflammation, bacterial and viral infections. However, scientific reports on Nepalese H. cordifolium are very limited. Here we report about the chemical screening of extracts, quality analysis of H. cordifolium extract by thin layer chromatography, TLC using H. perforatum extract and hyperoside as the standards, estimation of phenolics, flavonoids, tannins and sugars as well as antioxidant, antibacterial and cytotoxic activities of flower extracts. The ethyl acetate extract was fractionated and some phytochemicals were isolated. In our findings, TLC analysis of H. cordifolium extract showed the presence of chlorogenic acid, hyperoside and quercetin. Hypericine and rutin were not detected which indicated that the chemotaxonomy of H. cordifolium is different from H. perforatum. In phytochemical analysis, ethyl acetate extract showed the greater amounts of flavonoids, methanol extract showed the greater amounts of tannins and sugars and 50% aqueous methanol extract showed the greater amounts of phenolics. In DPPH free radical scavenging assay, ethyl acetate (18.79±0.98 μg/ml) and 50% aq. methanol (18.98±0.81 μg/ml) extracts showed the lower IC50 values than the methanol extract (27.00±1.03 μg/ml) due to the presence of high amounts of flavonoids and phenolics in these extracts. In antibacterial assay, all extracts showed moderate antibacterial activity against Staphylococcus aureus except 50% aqueous methanol extract. In cytotoxicity assay on human bladder carcinoma cell line 5637, ethanol extract showed IC50 value of 41.35±5.01 μg/ ml. Quercetin was isolated from ethyl acetate extract and characterized by UV and FTIR spectroscopy. The present findings indicated that the flowers of H. cordifolium could be the rich source bioactive compounds with antibacterial, cytotoxic and antioxidant activities.